Establishing Canada Geese in West Kent and their use of nesting rafts - Harrison, Jeffrey G; Harrison, Jeffrey G (Wildfowl, 1959)
In June 1956 the first 19 Canada Geese were collected from the Wildfowl Trust and placed on two industrial ballast waters, one of 10 acres, the other of 40 acres, about a mile apart in the Darenth valley near Sevenoaks. All the geese settled down at once and of the 12 placed on the larger water, four which were half-grown goslings were cared for by the adults, which appeared to make excellent foster-parents. Nine were feather pinioned to prevent wandering and by the end of the winter only one bird had left, although by early February a few were flying between the two waters and one pair moved to a third ballast water just to the west near Chipstead.